TEACHING SPEAKING SKILL THROUGH SMALL GROUP DISCUSSION TECHNIQUE AT THE ACCOUNTING STUDY PROGRAM - rivi antoni (Al-Manar : English and Arabic Journal, 2014)
This paper was the result of classroom action research that tried to answer the question how small group discussion technique could improve the students speaking skill and what factors influenced it. Frankly speaking, some English lecturers are only able to blame their students because of their limited skill in speaking English. In the other words, the lecturers rarely discuss about the technique used in the teaching process, especially speaking class. Though, lecturer also becomes a factor that determines whether or not the students can develop their speaking skills well. This researcher took second semester students of Accounting of Pasir P engarain University as his participant. This research was done in two cycles that each cycle consisted of 5 meetings with the test included. In the cycle 1, it was found that the students speaking skill got progress in two aspects only such as Vocabulary and grammar, while the other aspects are not well improved yet. That’s why the researcher did the cycle 2 as to improve the three aspects could not get better yet. After doing the second cycle, it was found that the students’ pronunciation, fluency and comprehension got progress. It could be seen from the speaking score achieved from the test given. The rule of friends found in small group discussion technique became the main factor that influences students’ speaking skill. Pertaining to the data analysis of the comparison of  based score with the two cycles. It could be concluded that Small group discussion better improved the students’ speaking skill at second semester students of Accounting of Pasir Pengarain University.